VII International Student Research Conference the Role of the Russian Language in International Relations - M. V. Belyakov (Концепт: философия, религия, культура, 2023)
On April 10, the 7th International Student Research Conference organized by the Russian Language Department was held at MGIMO University. This year the conference was devoted to the role of the Russian language in international relations. The conference was aimed at stimulating the research and project activities of young scientists in the field of studying the Russian language and its use in the field of scientific and professional communication. The opening plenary session included speeches by MGIMO professors M. V. Belyakov, A. A. Vasilyeva, N. D. Afanasyeva, and the Head of Science Department of RUDN U. M. Bakhtikireeva. The plenary session was followed by breakout sessions in two topic areas. The conference was attended by dozens of university students from Russia, from neighboring and distant foreign countries, including Turkey and China. Students delivered reports on various subjects, including the role of the Russian language in international politics and diplomacy, the Russian language in the context of the dialogue of cultures, the reflection of the national culture in the Russian language, the role of the Russian language in the post-Soviet space, etc. This event is held twice a year to give young scientists a venue to share the results of their research and serves as a discussion platform. Summing up, the participants noted the scientific and practical significance and relevance of the materials presented at the conference, the high professionalism of the speakers, the clear and high-quality organization of the conference, and expressed their gratitude to the organizers.